Physical and molecular characteristics of day 75 nuclear transfer cloned bovine conceptuses - De Lille, Alexandra, author; Seidel, George, advisor; Anthony, Russell, committee member; Clay, Colin, committee member; Garry, Franklyn, committee member (Colorado State University. Libraries, 2012)
This study was designed to measure fetal and placental characteristics in bovine day 75 nuclear transfer and control pregnancies. Responses included mRNA concentration of the insulin-like growth factor (IGF) system [IGF-1, IGF-2, IGF1R, IGF2R, IGFBBP-1, -2, -3] and the vascular endothelial growth factor (VEGF) system [VEGF, PlGF, VEGF1R, and VEGF2R]. Fetal attrition of the cloned pregnancies up to day 75 was high (89%, 63 out of 71 frozen embryos transferred; 8 of 16 cloned conceptuses present on day 30 survived to day 75, as did 5 of 5 controls). No significant differences in mean weights of large and medium placentomes were observed between 8 clones and 5 controls. However, the variance of mean weight of large placentomes was greater in clones than in controls; one gestation had placentomes six standard deviations larger than controls. Interestingly, the mean umbilical cord weight/length ratio was significantly greater for clones (P < 0.05). Mean fetal length, fetal weight, fetal weight/length index and mean weights for heart, brain, liver, kidneys and the mean brain/liver index did not differ between cloned and control day 75 conceptuses, but numbers per group were limited. Northern blot analysis, revealed the presence of three transcripts of 3.7kb, 2.2kb and 1.7kb for VEGF and one 1.7 kb transcript for PlGF mRNA in the cotyledons and allantochorion of day 45 cloned and control gestations. All three VEGF bands were present in both cloned and control day 75 cotyledons and caruncles, but the PlGF transcript was barely detectable, except for the cotyledons of one clone. mRNA for all of genes studied could be detected with real time PCR in day 75 cotyledons and caruncles, and fetal livers contained mRNA for all IGF's and IGFBP's evaluated. In all placentomal tissues, PlGF mRNA concentration was 100-fold less than VEGF mRNA, which seems to be the driving force for placentomal vascularization at day 75. There was a trend for a reduction by half of the PlGF mRNA concentration in caruncle of clones vs. controls (P = 0.06). VEGF2R (KDR) mRNA was abundant, but VEGF1R (Flt-1), was only present in very low concentrations; our primer set did not distinguish between soluble versus membrane bound receptor mRNA for VEGF1R. Four of the cloned conceptuses contained substantially less cotyledonary IGF1R mRNA than the other clones and controls. IGFBP-3 mRNA concentrations were very high in placentomes; IGFBP-1 and -2 mRNA concentration on the other hand was very low for clones and controls. mRNA for IGFBP-1, -2, -3, however, was abundant in day 75 fetal livers, while IGF-1 mRNA was scarce in this tissue. Fetal livers from cloned pregnancies contained 4-fold more IGF-2 mRNA than controls (P<0.01). We observed that liver IGF-2 mRNA concentration and liver weight increased with weight of the largest placentome; in clones these increases were associated with a decrease in cotyledonary IGF-2 mRNA, while the opposite occurred with controls. Interestingly, there was a trend to lower IGF2R mRNA concentrations (P = 0.09), and IGF-1 mRNA was twofold higher in cotyledons of clones (P= 0.03) compared to controls. For many measurements, means were not significantly different (P > 0.1) between clones and controls. However, unequal variances were common, and data points with statistical outlier behavior were observed for clones, which highlights the heterogeneity of the cloned population. This variation in gene expression may exacerbate abnormal placentation later in gestation, and might explain some of the increased morbidity and mortality seen in calves resulting from cloning by nuclear transfer.
Keywords: nuclear transfer cloning; insulin like growth factor; placenta; angiogenesis; bovine